Tert-Butyldimethylsilyl Amine (TBDMS-NH2): A Mild and Green Reagent for the Protection of Benzyl Alcohols, Phenols, and Carboxylic Acids under Solvent-Free Conditions - Duczynski, J.; Fuller, Rebecca; Stewart, S. (CSIRO Publishing, 2016)
© The Authors 2016. Herein, we present the use of the tert-butyldimethylsilyl amine (TBDMS-NH2) as a silylating reagent for phenols, benzyl alcohols, and carboxylic acids. Unlike other silyl protection reactions, this reported process with TBDMS-NH2 does not involve the formation of HCl. Importantly, we report the efficacy of this reagent in operating under solvent-free conditions and enabling short reaction times.